Risk of falls among patients treated in a hospital service in Quixadá County, Brazil (Brazilian Journal of Health Research, 2019)
Introduction:The quality of safety control of patients admitted to health services is one of the priority concerns of health systems. Among the reasons that lead to the drop in the safety of care provided to patients in the hospital environment are falls. Therefore, patient safety in the prevention of falls has been one of the topics of investigation. Objective: Evaluating the risk of falls among patients treated in a hospital service in Quixadá County, Ceará State. Methods: Documentary study applied to the medical record of 50 patients treated at the municipal hospital of Quixadá County – Ceará State in January and February 2018, based on a form built in compliance with the Fall Prevention Protocol by the Ministry of health. Data were tabulated in order to generate tables with absolute frequencies and percentages, which were later analyzed in the Epiinfo 7.0 software. Results: The characterization of the studied population has shown that 56.0% were women, 42.0% were 60 years old or older, 42.0% were married/lived in common-law marriage, presented normal BMI (34.0) and featured different indicative diagnoses for hospitalization, such as urinary tract infection (10.0%), cerebrovascular accident (8.0%), infected venous ulcer (8.0%), among others. Factors associated with more than 50.0% risk of falls were: demographic profile of elderly individuals older than 65 years (72.0%); health conditions and incidence of chronic diseases (84.0%); changed functionality (60.0%), sensory impairment (56.0%); and “polypharmacy” treatment (70.0%). Based on the classification of the level of risk of falls among patients treated in the health service, all patients presented high risk of falls (100.0%); this risk was characterized by patients’ dependence on third-parties to carry out their activities, regardless of the presence of any risk factor; and by the fact that they needed help to walk (52.0%). Conclusion: The present study can be used by health services as basis to analyze how patient care has been provided, as well as to plan improvements to be implemented during hospitalization in order to reduce the burden to patients’ health, to their family members and to the Government.